Quantitative Imaging in Diffuse Liver Diseases - Van Beers, Bernard E.; Garteiser, Philippe; Leporq, Benjamin; Rautou, Pierre-Emmanuel; Valla, Dominique (Seminars in Liver Disease, 2017)
Cross-sectional imaging methods and more specifically ultrasonography and magnetic resonance imaging (MRI), have increasing roles in the quantitative evaluation of diffuse liver diseases. Particularly, ultrasound elastography is becoming the standard first-line examination for diagnosing severe liver fibrosis. Quantitative ultrasonography also brings information for staging portal hypertension in compensated cirrhosis and for grading liver steatosis. Quantitative MRI offers a multiparametric approach to assess the severity of liver steatosis, iron overload, fibrosis, inflammation, and portal hypertension. Regional liver transport function can be assessed with combined volumetric computed tomography and 99Tc mebrofenin single-photon emission computed tomography or with gadoxetic acid-enhanced MRI. It is concluded that multiparametric MRI complements the information brought with quantitative ultrasonography and has the potential to become a method of virtual liver biopsy that may decrease the need for invasive reference examinations in diffuse liver diseases.
Keywords: liver magnetic resonance imaging; liver ultrasonography; liver elastography; chronic liver disease; liver cirrhosis